Sexualidad y discapacidad: percepcion social - Hoyos Córdova, Liliana Marisela (Machala : Universidad Técnica de Machala, 2017)
El presente trabajo analítico descriptivo de investigación se desarrolló con miras a discapacidad, valiéndose para tal objetivo de una modalidad metodológica mixta es decir del conjunto de herramientas del método cuantitativo así como de valoraciones cualitativas que permitieron la construcción de un marco teórico conceptual acerca de las creencias de la sociedad en cuanto a las personas con discapacidad, así como la calidad de vida desde el área sexual y social de las mismas. La línea teórica en la que se basó la construcción conceptual de la presente investigación es de enfoque familiar sistémico, modelo orientado a la identificación etiológica de la caracterización sintomática del individuo desde su entorno o contexto sobre todo familiar, comprendiendo como la estructura familiar ha de incidir sobre el modo comportamental de cada persona, es decir el sistema familiar modula la interacción de las personas dentro del mismo sistema, así como con los sistemas circundantes, más aun al referirse a temas como la discapacidad,
The present descriptive analytical research work was developed with a view to disability, using for that purpose a mixed methodological method ie the set of tools of the quantitative method as well as qualitative assessments that allowed the construction of a theoretical framework conceptual about the beliefs Of society in terms of people with disabilities, as well as the quality of life from the sexual and social area of ​​the same. The theoretical line on which the conceptual construction of the present research was based is a systemic family approach, a model oriented to the etiological identification of the symptomatic characterization of the individual from his / her environment or family context, understanding how the family structure has to influence On the behavioral mode of each person, ie the family system modulates the interaction of people within the same system, as well as surrounding systems, more so when referring to issues such as disability, understanding that the support required is greater to achieve A functional development, if that is added to the theme of sexuality, the problem is compounded by being a taboo subject in society increasing inadequate and ignorant mental schemes causing problems in the area of ​​sexual, social, family and work, is For that reason that understanding the relevance of this social theme, in the present work the scales of: Scale of social perception towards people with Down syndrome adapted to the intellectual disability, Scale of adaptability and family cohesion.
Keywords: DISCAPACIDAD; SEXUALIDAD; FUNCIONALIDAD; DISCRIMINACION